2018
DOI: 10.1038/micronano.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

A designable surface via the micro-molding process

Abstract: A rapid prototyping process was presented to fabricate a nylon honeycomb microstructure coated with parylene C. The surface structure was designed to obtain a hydrophobic surface using the volume of fluid (VOF) model. With the micro-molding technique, the contact angle of the polymer surface could be designed and fabricated by changing the different microstructure surface diesteel mold inserts. For the honeycomb (20 μm width and 60 μm depth) microcavity side wall, an average micro-molding filling percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This rapid prototyping technology can make more designable microstructures on polymer surfaces. [ 176 ] Song et al fabricated microstructures on oxygen‐free copper and 304 stainless steel by imprinting. [ 177 ] Li et al manufactured nanoporous TiO 2 films with diverse pore sizes on smooth titanium foil by a two‐step anodic oxidation process.…”
Section: Fabrication Methods Of Bionic Microstructure Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…This rapid prototyping technology can make more designable microstructures on polymer surfaces. [ 176 ] Song et al fabricated microstructures on oxygen‐free copper and 304 stainless steel by imprinting. [ 177 ] Li et al manufactured nanoporous TiO 2 films with diverse pore sizes on smooth titanium foil by a two‐step anodic oxidation process.…”
Section: Fabrication Methods Of Bionic Microstructure Surfacementioning
confidence: 99%
“…The drag reduction effect of the specimens can be obtained by comparing the results. [176,205] Toloui et al observed and analyzed the turbulent flow and roughness deformation around a rigid and flexible cylinder microstructure by digital inline holographic particle tracking velocimetry (DIH-PTV). [206] Utilizing high-resolution PIV measurement combined with refractive-index matching (RIM) technique, not only was the turbulence on a hemispherical array studied, but also the flow near a single roughness element was successfully observed.…”
Section: Pivmentioning
confidence: 99%
“…The super hydrophobic or super hydrophilic design of micro surfaces can be well used in medical devices, especially the local microenvironment (topography and strength) can decisively affect the ability of cells to self-renew and differentiate ( Yatsushiro et al, 2016 ; Shiu et al, 2018 ). Wang et al ( Wang et al, 2018 ) fabricated honeycomb-like micro surface arrays with different contact angles by means of micro-injection ( Figure 6A ). Li et al ( Lee et al, 2019 ) successfully achieved the preparation of curved parts with sub-micron surface morphology through micro-injection and nano-imprinting ( Figure 6B ).…”
Section: Micro Injection Moldingmentioning
confidence: 99%
“…Due to simple manufacturing and installation, coatings are widely applied to change the surface characteristics of materials. 29,166 Both the drag-reduction surface and the hydrophobic surface are based on the microstructure, and the combined effect of the two has been extensively researched and manufactured. Dou et al utilized the coating technology to create a bionic surface to reduce the drag.…”
Section: Coating Technologymentioning
confidence: 99%